PENGARUH PENGGUNAAN TATA BAHASA MODUL PRAKTIKUM DAN PENGGUNAAN BAHASA OLEH ASISTEN LABORATORIUM MEKANIKA TANAH TEKNIK SIPIL UPN "VETERAN" JAWA TIMUR TERHADAP PEMAHAMAN MAHASISWA PADA KEGIATAN PEMBELAJARAN PRAKTIKUM - Sholihatin, Endang; Saputra, Novaldi Rizky; Silalahi, Dumaris (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
Practicum is an important aspect of learning in higher education, especially in engineering. At UPN "Veteran" East Java, Civil Engineering students are required to take part in soil mechanics laboratory practicum. Language serves to convey one's thoughts and feelings. Language error is when a language deviates from the standards commonly used by native speakers. This type of language error can stem from a violation of a common language system or language habits that can hinder communication. However, students experience obstacles in understanding practicum material due to the language used by laboratory assistants and learning modules that are less effective. This research aims to: 1) To determine the use of grammar in the practicum learning module of the soil mechanics laboratory at UPN "Veteran" East Java; 2) To find out how effective the use of language by laboratory assistants is on students' understanding of soil mechanics laboratory practicum activities at UPN "Veteran" East Java. The conclusions of this study are: 1) The use of grammar in the soil mechanics laboratory practicum learning module at UPN "Veteran" East Java is not fully in accordance with the EYD because it was found that there were 191 error data in the form of words in the Soil Mechanics Practicum Module for the 2023/2024 Academic Year which included 70 typing errors, 23 errors in the use of prepositions or prepositions, 24 errors due to using non-standard words,  67 errors in writing foreign languages, and 7 errors in the use of numerical and sequence indicators. 2) The use of language by laboratory assistants on students' understanding of soil mechanics laboratory practicum activities at UPN "Veteran" East Java has proven effective, it is shown that a) As many as 70.6% of the total respondents have been helped by the effectiveness of using clear, concise, and easy-to-understand sentences; b) As many as 56.5% of respondents were helped by the use of practicum tools, such as diagrams, tables, and graphs in the UPN "Veteran" East Java Civil Engineering Soil Mechanics Practicum Module for the 2023/2024 Academic Year; c) The majority of respondents, 68.2%, had sufficient opportunity to ask questions and discuss with laboratory assistants to clarify respondents' understanding during practicum; d) As many as 70.6% of the total respondents did not choose the option very suitable in question number 4, namely "How appropriate is the explanation given by the laboratory assistant with the explanation contained in the practicum module?" Because there are differences in the number of practicums carried out during practicum and those contained in the practicum module. Therefore, it is necessary to update the existing modules so that there is a compatibility between the practicum carried out with the explanation of the practicum contained in the module and make improvements to the writing in the latest module so that there are no misunderstandings by students who will do soil mechanics practicum at UPN "Veteran" East Java.Keywords: Language, Soil Mechanics Practicum Module, Laboratory Assistant, Civil Engineering UPN "Veteran" East Java